Neuropathic ulcers in leprosy treated with intralesional platelet‐rich plasma - Conde‐Montero, Elena (Int Wound J, 2014)
Neuropathic ulcers in leprosy represent a therapeutic challenge for clinicians. Chronic ulcers affect patient health, emotional state and quality of life, causing considerable morbidity and mortality in addition to contributing to significant health care costs. The pathogenesis is mainly related to the abnormally increased pressure in areas such as the sole of the foot, secondary to lack of sensation and deformities induced by peripheral sensory‐motor neuropathy. Conventional treatment of these wounds can be slow due to their chronic inflammatory state and the senescence of local reparative cells. Platelet‐rich plasma (PRP) may restore the healing process, leading to a reparative phase. We present two patients with four neuropathic leprosy ulcers that have responded satisfactory to PRP treatment. PRP therapy has been growing as a viable treatment alternative for chronic ulcers. However, stronger scientific evidence is required to support its potential benefit for use in chronic wounds.